Resisting temptation and its relationship to the mature personality of university students (Journal of the College of Basic Education, 2022)
Universities are among the basic ingredients for the formation of a person who is able to use his mental abilities adequately in facing different life situations and to make the right decisions in his work, university, and others (Hassan, 1989: 22).University youth are exposed to many tempting situations that may push them to engage in behavior that is contrary to the social standards and moral values ​​prevailing in society. We fear for them, as future leaders, that their resistance to temptation may weaken, which may lead to their psychological incompatibility, and that weak resistance to temptation among university youth may affect In their personalities, their conscience may shake or make them feel guilty, which may make them deal with the events that university youth face in a positive way.